(untitled) (Research, Society and Development, 2021)
Brazil is an agricultural country and extremely dependent on chemical fertilizers from the international market. Soil remineralization is an important solution for nutrient recovery from land subjected to intense cultivation or weathering and leaching processes, especially in tropical regions. Thus, the objective of this article was to demonstrate the importance of remineralizers as a sustainable alternative for soil fertilization in Brazil, through a bibliographical review, analysis of the current legislation and official public data. Law 12,890/2013 included remineralizers as a category of input for agriculture and Normative Instruction No. 05/2016 published by the Ministry of Agriculture, Livestock and Supply (MAPA) regulated this new agricultural input. The research and employment of rockstone techniques has increased, including registration in the MAPA of companies producing remineralizers in some Brazilian states, such as Minas Gerais, Goiás and Paraná. And although Pará has national prominence in mineral production, there is still no record of production of this input in the state, which makes it necessary to develop research into the use of rock powder in the region. The stonemeal technique brings benefits such as significantly lower costs than conventional fertilizers; increased agricultural production; absence of environmental impacts to the soil and water bodies; in addition to the use of mineral residues. Considering the Brazilian geodiversity, remineralizers tend to become an agricultural input of great availability in the country, allowing the reduction of its external dependence on fertilizers, bringing social, economic, productive and environmental benefits to the country.